The convergence of monetary policy between candidate countries and the European Union - Josef C. Brada; Ali M. Ktan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
We compare the convergence with German monetary policy of the monetary policy of transitioneconomy candidates for EU membership, of non-transition candidates and of countries that have recently joined the EU. We find significant long- and short-run linkages between German base money stock and that of the most recent members of the EU; the same holds true for the nontransition economy candidates. Among the transition economies, the ability to follow the policies of the Bundesbank is weaker or, for some countries, nonexistent. Such weak policy coordination may reflect the need for building up the financial sectors of these countries and allowing for a period in which they tie their policies more closely to that of the ECB.
Keywords: 330